2016
DOI: 10.1039/c6ra06103f
|View full text |Cite
|
Sign up to set email alerts
|

Poly(norbornyl-NDIs) as a potential cathode-active material in rechargeable charge storage devices

Abstract: Two pendant-type naphthalene diimide (NDI) polymers bearing a polynorbornene backbone were prepared and their electrochemical properties explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This is possibly due to the fast kinetics giving cyclic voltammogram curves present serious peak overlap and the discharge/ charge curves present only one plateau. [7,25] The coulombic efficiencies (the ratio of discharging versus charging capacity) were over 98% for both polymers at lower C rates. The cyclic voltammograms of coin cells of 5 showed hardly any change in the current over 500 cycles, however, for polymer 6, a slight decrease in current was observed (see Fig.…”
Section: Research Lettermentioning
confidence: 97%
See 2 more Smart Citations
“…This is possibly due to the fast kinetics giving cyclic voltammogram curves present serious peak overlap and the discharge/ charge curves present only one plateau. [7,25] The coulombic efficiencies (the ratio of discharging versus charging capacity) were over 98% for both polymers at lower C rates. The cyclic voltammograms of coin cells of 5 showed hardly any change in the current over 500 cycles, however, for polymer 6, a slight decrease in current was observed (see Fig.…”
Section: Research Lettermentioning
confidence: 97%
“…There have been various efforts focused on increasing cyclability by introducing rigid aromatic groups, [3,4] insoluble salts, [5] and macromolecular materials. [6][7][8][9][10][11][12] Polymers can be designed to be insoluble in electrolyte solution while still retaining the high theoretical capacity (C theor ) of small molecules. As a result, polymer-based materials with carbonyl groups have gained popularity, such as anhydrides and quinones which have proven to achieve significant progress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pendant-type naphthalene diimide-based polymer bearing a N-methyl group (N-methyl-N0-(50-norbornene-20-methyl) naphthalene-1,4,5,8-tetracarboxylic diimide) delivered a capacity of 138 mAh g −1 at 5C, which suggested that almost all of the NDI moiety contributed to charge storage, and 96 mAh g −1 at 20C. Most of all, the capacity retention at 10C was 90% over 1000 cycles [176]. The electrochemical measurements were performed under nitrogen and with 0.1 mol L −1 tetrabutylammonium hexafluorophosphate in CH 2 Cl 2 as the electrolyte.…”
Section: Imides-dianhydridesmentioning
confidence: 99%
“…Redox-active polymers have been attracting considerable attention as the key components of various energy-related devices such as charge storage devices, displays, memories, and solar cells due to their splendid electrochemical characteristics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In particular, electrochromic (EC) polymers represented by polyviologens, polythiophenes, and metallopolymers show high contrast accompanied with reversible redox reactions [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%